Experimental Breeding of Rare Medicinal Plant Parkia roxburghii G. Don. - Siswoyo .; Ekarelawan .; Ervizal A.M Zuhud (Media Konservasi, 1993)
Kedawung (Ptukia roxburghii G. Don.) is a rare species of medicinal plants. Seeds of this plant are useful to relieve several types of stomach disorders, including cholera.The objective of this study is to examine the effect of several kinds of fertilizers, i.e. compost, "dekastar", droppings of goats and chicken, on the growth of seedlings on latosol soil type. It is expected that the result will give information about the best composition of fertilizer to produce maximum growthof Kedawung seedlings.The result showed that a medium with N composition (40 % soil + 60 % compost) gave the bestresult. Height and diameter increased by 46 %, 16 % and 148.08 % compared to media with 100 % soils.Media N, H (SO % soil and 20 % chicken droppings) and J (60 % soils + 40 % goat droppings) gave similar effect on the height increment of seedlings. The use of compost in various compositions did notshow a significant effect on the diameter growth of Kedawung seedlina.s.